2011
DOI: 10.1038/ejhg.2011.182
|View full text |Cite
|
Sign up to set email alerts
|

De novo deletions and duplications detected by array CGH: a study of parental origin in relation to mechanisms of formation and size of imbalance

Abstract: We report a large series of 173 patients with physical and/or neurological abnormalities and a de novo imbalance identified by array CGH. Breakpoint intervals were screened for the presence of low copy repeats (LCRs) to distinguish between rearrangements formed by non-allelic homologous recombination (NAHR) and rearrangements formed by other mechanisms. We identified significant differences in size and parental origin between the LCR-mediated and non-LCR groups. Non-LCR imbalances were evenly distributed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Such a predominant sporadic occurrence along with the seemingly exclusive paternal derivation of rea(X) chromosomes (see below) may predict an advanced paternal age at the patients' conception. Yet, the mean paternal age in 10 sporadic rea(X) cases (including 7 de novo but just 1 of proven paternal descent) was 32.50 years, a figure in agreement with the lack of a paternal age effect in large and submicroscopic de novo imbalances [Thomas et al, 2006;Lupski, 2007;Sibbons et al, 2012]. Of note, among 10 rea(X) chromosomes (including 4 with dup p, 6 with dup q; 8 of these proved to be de novo) whose parental origin was elucidated, 9 were paternal.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Such a predominant sporadic occurrence along with the seemingly exclusive paternal derivation of rea(X) chromosomes (see below) may predict an advanced paternal age at the patients' conception. Yet, the mean paternal age in 10 sporadic rea(X) cases (including 7 de novo but just 1 of proven paternal descent) was 32.50 years, a figure in agreement with the lack of a paternal age effect in large and submicroscopic de novo imbalances [Thomas et al, 2006;Lupski, 2007;Sibbons et al, 2012]. Of note, among 10 rea(X) chromosomes (including 4 with dup p, 6 with dup q; 8 of these proved to be de novo) whose parental origin was elucidated, 9 were paternal.…”
Section: Resultssupporting
confidence: 68%
“…The parental and inter-or intrachromosomal derivation as well as the underlying mechanism in most recombinant-like autosomes is unknown; among 14 cases with identified parentage, paternal and maternal descent were equally frequent. In comparison, there were 8 interchromosomal and 15 intrachromosomal cases among 23 autosomal duplications (11 paternal, 12 maternal) not due to rec-like chromosomes [Sibbons et al, 2012]. Of note, 1 acquired [Hecht et al, 1984] dup q and 2 constitutional rea(1) chromosomes (cases 2 and 10) have been associated with cranial teratoma, acute leukemia, and Wilms tumor, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…We found that they were equally likely to be maternal or paternal in origin and that they were not associated with any parental age effect. In both these respects, they are the same as the common conditions such as DiGeorge and Williams syndromes, which is hardly surprising as they all appear to result from the same mechanism (43).…”
Section: The Origin Of Structural Chromosome Abnormalitiesmentioning
confidence: 78%
“…These are detected using fluorescence in situ hybridization or, more recently, array comparative genomic hybridization (aCGH). We and others have shown that the origin of many of the more common microdeletion and microduplication syndromes-e.g., DiGeorge syndrome and Williams syndrome-is equally likely to be maternal or paternal, and there appears to be no effect of parental age (43).…”
Section: The Origin Of Structural Chromosome Abnormalitiesmentioning
confidence: 98%
“…44 In another study, de novo imbalances not mediated by low copy repeats were significantly more often of paternal than of maternal origin. 45 Thus, to date, although there is no strong evidence supporting an imprinting mechanism in the 6q16 region, a parent-of-origin effect cannot be excluded, as none of the three maternally derived deletions, which were currently reported, (patient no. 11, 14, and case 4 from Bonaglia et al report) 13 was associated with PWS-like features.…”
Section: Clinical and Fetopathological Datamentioning
confidence: 94%